(untitled) (Applied Biological Research, 2022)
The present study was aimed to assess the length-weight relationship and condition factor of exotic common carp (Cyprinus carpio). The morphological measures i.e., total length and weight of randomly selected 306 specimens of common carp, obtained from from Atgam village pond Valsad (Gujarat), were measured in January 2021. The fish were divided into four length groups i.e., A, B, C and D at length distance of 5.0 cm. The result showed that the fish length and weight in population was in the range d 205 to 259 g, respectively. The length frequency was 34, 79, 104 andthat lgroup C was dominant in the population, followed by group D, B and A. The length and weight variables were positively correlated (r2 = 0.886) and growth constant or regression coefficient was 2.804 revealing that the growth ofish was negative allometric that was considered abnormal growth as the weight increment was less with respect to fish length. The mean value of condition factor for group A, B, C, D and pooled population were 1.77 ± 0.03, 1.29 ± 0.01, 1.41 ± 0.02, 1.40 ± 0.01 and 1.41 ± 0.01, respectively, which indicated that the condition of fish was good in the aquatic environment. The information generated may help in ecological and biological management of fish for enhanced production and revenue generation in village ponds.